THE EFFECT OF FIRM CHARACTERISTIC ON INTELLECTUAL CAPITAL DISCLOSURE IN ISLAMIC BANKING: EVIDENCE FROM ASIA - Tri Damayanti; Ayu Budiyanawati (Institute for Research and Community Empowerment (LPPM TAZKIA), 2009)
This research aims to investigate the relationship between firm’s characteristic (firm size, profitability, leverage, and company age) and intellectual capital disclosure. This research also uses control variables such as board size, firm’s audit, and role of duality. Sample in this research are 34 Islamic bank’s annual reports collected by pooled data. Dependent variable in this research is intellectual capital disclosure. Dependent variable is measured by content analysis method. Content analysis is supported by disclosure index that measured variety of intellectual capital disclosure. It is also supported by word count that represented volume of intellectual capital disclosure respectively. Independent variable in this research are firm’s characteristic, consists of firm size, profitability, leverage, and company age. Data are analyzed by using SPSS program 16.00 version. Result of analysis indicates that there exist a significant relationship between variety of intellectual capital disclosure with all firm characteristic except for firm’s size. In other side, there is significant association volume of intellectual capital disclosure with all firm’s characteristic except for profitability. The influence of firm characteristic on intellectual capital mechanism on human, structural, and relational capital disclosure, based on two matrixes, is also explored.Keywords : Firm Characteristic, Intellectual Capital Disclosure, Content Analysis, Islamic Banking